Sensory evaluation of Chinese white salted noodles and steamed bread made with Australian and Chinese wheat flour - Liu, R.; Solah, Vicky; Wei, Y.; Wu, G.; Wang, X.; Crosbie, G.; Fenton, Haelee (A A C C International, 2018)
© 2018 AACC International, Inc. Background and objectives: Chinese white salted noodles (CWSN) and steamed bread (CSB) are staple foods and represent approximately 65% of wheat consumption in China. Sensory evaluation was used to measure the quality attributes of selected Australian wheat varieties and Chinese commercial wheat for Chinese white salted noodle and northern style steamed bread. Descriptive parameters for Chinese sensory evaluation are described and tested using a Chinese-trained expert sensory panel. Findings: The results showed that flour from selected Australian wheat varieties had better gluten properties, dough mixing characteristics and starch properties compared with the commercial Chinese wheat flours evaluated. Improved sensory evaluation scores in noodle firmness, stickiness, elasticity, smoothness, and flavor resulted in a significantly higher total quality score (p < 0.05) for all Australian wheat flours and blends (60% and 74% extraction) compared with the two Chinese wheat flours for CWSN. Sensory evaluation scores for steamed bread from the Australian wheat variety Mace (60% and 74% extraction) were equal to the best Chinese gold standard flour (49% extraction) and significantly higher (p < 0.05) than Chinese flour of 69% extraction. The Australian flours with protein content 9%–10.5% produced higher quality white salted noodles and steamed bread than the higher protein 12.0% Chinese flours. The highest scoring noodles at 78.5–79.5 points were Australian Mace, and Mace and Zen blends. The highest scoring Chinese steamed bread at 85.7 points was Mace at 60% extraction. Conclusions: The features of the Australian 60% extraction flours were higher noodle firmness, elasticity, and smoothness scores and improved flavor compared with the 49% extraction Chinese gold standard flour. Noodle sensory evaluation results showed significantly higher (p < 0.05) total scores for the Australian flours compared with noodles made with the two high-quality Chinese wheat flours. The features of Australian 60% extraction flour were ideal for steamed bread characteristics: mouthfeel, stickiness, texture, and elasticity/firmness. Steamed bread made from Mace flour (60% and 75% extraction) showed a significantly higher total score compared with steamed bread made from Chinese wheat flour (69% extraction). The demand for improved wheat quality in China is growing, and future research is needed to investigate quality of newly released Australian and Chinese wheat varieties. Significance and novelty: This research contributes to defining sensory quality testing methods and quality characteristics for Chinese white salted noodles and steamed bread. Mace and Zen blends were tested for sensory quality by a Chinese expert sensory panel.